Cultural Value And Education Value in Kembara Rindu Novel by Habiburrahman El Shirazy and Anak Rantau Novel By A. Fuadi - Marzuan, Marzuan; Missriani, Missriani; Fitriani, Yessi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to examine the cultural and educational values ??in the KembaraRindunovel by Habiburrahman El Shirazy and the AnakRantau novel by A. Fuadi. The method used is the descriptive qualitative method. Based on the results of the research data analysis, it is illustrated that in the two novels studied there are cultural values ??which include: (1) cultural values ??in human relations with God, (2) cultural values ??in human relations with nature, (3) cultural values ??in human relations with society, (4) cultural values ??in human relations with human, and (5) cultural values ??in human relations with oneself. The educational values ??contained in the two novels are (1) the value of religious education, (2) the value of moral education, (3) the value of social education, and (4) the value of cultural education. Therefore, the study of cultural values ??and educational values ??in the novel contains an overview through characters and characterizations.